Purchase intention of smartphone among youth in Shah Alam - W Ab Rahim, Wan Norsyahirah (2017)
This research is focusing on the purchase intention of smartphone among youth in Shah Alam. The purpose of the study is to identify the most influential factor that influence the purchase intention of smartphone among youth and to examine the factors that influence purchase intention of smartphone which are price, brand name, product features and social influence. In order to attain and accomplish the objectives of this study, research questions and four hypotheses are developed and tested. This study employ survey research design and primary data are collected by distributing the questionnaire to the target respondents which is youth respondents aged from 15 years old to 40 years old in Shah Alam. 302 respondents were collected by using convenience sampling method. The data collected from the respondents were analyzed by using the Statistical Package for Social Science (SPSS) version 21. In this research, it was found out that brand name and social influence has significant relationship on purchase intention of smartphone among youth in Shah Alam. Meanwhile, price and product features has no significant relationship on purchase intention of smartphone among youth in Shah Alam. Recommendations and directions are provided to assist the future researcher to conduct their research.